Psychoanalytic psychotherapy : a practitioner's guide - McWilliams, Nancy (Colección de libros electrónicos de ULoyola, 2004)
Addressing the art and science of psychodynamic treatment, Nancy McWilliams distills the essential principles of clinical practice, including effective listening and talking; transference and countertransference; emotional safety; and an empathic, attuned attitude toward the patient. The book describes the values, assumptions, and clinical and research findings that guide the psychoanalytic enterprise, and shows how to integrate elements of other theoretical perspectives. It discusses the phases of treatment and covers such neglected topics as educating the client about the therapeutic process, handling complex challenges to boundaries, and attending to self-care. Presenting complex information in personal, nontechnical language enriched by in-depth clinical vignettes, this is an essential psychoanalytic work and training text for therapists.